Formative gender evaluation: technical report on the viable sweetpotato technologies in Africa - Tanzania project. - Mudege, Netsayi N.; Grant, F. (International Potato Center, 2017)
This report is based on a qualitative formative gender evaluation of the Viable Sweetpotato Technologies for Africa (VISTA) Tanzania project implemented in seven districts in the Mbeya, Iringa and Morogoro regions, which are part of USAID’s (United States Agency for International Development) Feed the Future zone of influence. VISTA Tanzania seeks to contribute to improved dietary diversity, food security and incomes in Tanzania, especially among households with children under five years of age; expand the production, consumption, storage, utilization and marketing of orange‐fleshed sweetpotato (OFSP) and its products; and create financially viable sweetpotato seed and root enterprises to improve the sweetpotato value chain.